Practice-Centered Education in Higher School - V. A. Starodubtsev (Высшее образование в России)
The development of practice-centered education is attributable to the needs of widely understood social practices, framed as a demand of the economic sphere in highly qualified personnel with certain skills and qualification profile. Today, the employers expect from educational organizations more than just graduates familiar with industry and having a  good theoretical background, but the employees who are able to perform  various tasks relating to production, design or organizational issues from the first days of entry on duty. Therefore, the educational process in the engineering university should be organized to ensure the conditions for students to perform certain types of work (professional tryouts) related to future professional activities. It is necessary to develop and build on practical skills and competences in line with the educational program. The student’s professionally oriented activity is viewed as a type of educational and work activity aimed at the professional development of a person achieved though gaining experience in using means and methods of professional activity in the social environment. The basis of this educational process is practice-centered education. The article examines the existing models of practice-centered training (PCL) such as dual education, sandwich courses, social partnership between university and enterprise, learning through volunteering,  project activity, analyzes their merits and possible risks.